Monitoring Grameenphone value chain suppliers in light of health, safety, security and environment (HSSE) & Labor code-2006 - Mafiz, Tahnia (BRAC University, 2012)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2012.